Exercise-Induced Irisin and Its Role in Metabolic and Neurological Adaptations: A Narrative Review - Malec, Julia Anna; Kulig, Lidia; Winiarska, Zuzanna; Woźniak, Weronika Maria; Wieleba, Marcin; Krupska, Barbara Izabela; Zapalska, Magdalena; Steć, Sara; Wiercioch, Eliza; Włodarczyk, Franciszek (Quality in Sport, 2026)
Background. In the context of the increasing prevalence of metabolic and neurodegenerative disorders, growing attention has been directed toward biological factors mediating the beneficial effects of physical activity. Among them, irisin, a myokine released in response to muscle contraction, has emerged as a potential regulator of metabolic and neurological processes. Its role in inter-tissue communication and adaptation to exercise has become a subject of intensive research. Aim. The aim of this study was to summarize the current state of knowledge regarding exercise-induced irisin and its role in metabolic and neurological adaptations. Material and methods. A narrative review was conducted using the PubMed and Web of Science databases. The analysis included systematic reviews as well as experimental and clinical studies published between 2017 and 2026 focusing on the role of irisin in metabolism, nervous system function, and responses to physical activity. Results. Available evidence indicates that irisin is involved in the regulation of glucose and lipid metabolism, improvement of insulin sensitivity, and induction of browning of white adipose tissue. Additionally, irisin appears to exert neuroprotective effects by influencing brain-derived neurotrophic factors (BDNF), supporting neurogenesis and cognitive function. Physical activity, particularly its intensity, type, and duration, plays a key role in modulating circulating irisin levels. However, the findings across studies remain inconsistent, likely due to methodological differences and variability in study populations. Conclusions. Irisin may represent an important link between physical activity and its beneficial metabolic and neurological effects. Nevertheless, due to the heterogeneity of existing evidence, further well-designed studies are needed to better understand its mechanisms of action and potential clinical applications.